Cochlear implantation in extraordinary cases - Çelenk, Fatih; Cevizci, Raşit; Altınyay, Şenay; Bayazıt, Yıldırım Ahmet (AVES, 2015)
Background: Although cochlear implantation has been almost a standard otological procedure worldwide, it may still create a dilemma for the surgeon in some unusual instances such as Seckel syndrome, aural atresia and posterior fossa arachnoid cyst. Case Report: Three extraordinary cases of cochlear implantation were reported. The first case was a case of Seckel syndrome with a cardiac pacemaker due to complete atrioventricular block. The second case had posterior fossa arachnoid cyst that had retrosigmoid cyst removal and cochlear implantation simultaneously. The last case had cochlear implantation in the ear with congenital aural atresia. All cases could be implanted successfully with full electrode insertion and good audiological outcome. Delayed facial paralysis that occurred in the patient with arachnoid cyst resolved spontaneously. Conclusion: This study addressed the efficiency of cochlear implantation in cases of Seckel syndrome, complete atrioventricular block managed with cardiac pacemaker, congenital aural atresia and posterior fossa arachnoid cyst. In addition, the retrosigmoid approach and cochlear implantation can be performed simultaneously.
Keywords: Cardiac Pacemaker; Cochlear Implant; Congenital Aural Atresia; Seckel Syndrome; Subarachnoid Cyst